2015
DOI: 10.3233/bme-151359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vibration on muscle strength imbalance in lower extremity using multi-control whole body vibration platform

Abstract: Abstract. This study shows the improvement of muscle activity and muscle strength imbalance in the lower extremities through independent exercise loads in vibration platform. Twenty females of age 20 participated in this study. The subjects were divided into WBV group, with more than 10% of muscle strength imbalance between left and right the lower extremities, and control group, with less than 10% of muscle strength imbalance between left and right the lower extremities. As the prior experiment showed, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…It has been suggested that hamstring strengthening improves joint stabilization and reduces the risk of lower limb injury [38]. Since vibration training reduces strength asymmetry between the quadriceps and the hamstrings (as confirmed – in our study – by a tendency of the H/Q ratio to increase) and improves muscle strength imbalance between the lower extremities [39] it might be used for prevention and rehabilitation in patients with muscle and knee joint injuries including anterior cruciate ligament injury [13]. …”
Section: Discussionsupporting
confidence: 77%
“…It has been suggested that hamstring strengthening improves joint stabilization and reduces the risk of lower limb injury [38]. Since vibration training reduces strength asymmetry between the quadriceps and the hamstrings (as confirmed – in our study – by a tendency of the H/Q ratio to increase) and improves muscle strength imbalance between the lower extremities [39] it might be used for prevention and rehabilitation in patients with muscle and knee joint injuries including anterior cruciate ligament injury [13]. …”
Section: Discussionsupporting
confidence: 77%
“…In contrast, the whole-body vibrations are used in modern medicine for training and rehabilitation, increasing muscle tone and circulation, improving bone and neuromuscular functions, knee flexion, better muscle performances, speed up recovery period (after long period of exercise or similar) among others (Martinez-Pardo et al 2014;Pel et al 2009;Torvinen et al 2002;Yu et al 2014). For this purpose, vibrating platforms are used on which a subject stands and through the changing of frequency (0-50 Hz) (Yu et al 2015), the oscillation amplitude (0 -9 mm) and angles of the knee (30 0 , 60 0 , 90 0 ) (Avelar et al 2013;Ritzmann et al 2013), the above described positive results are obtained. During the bus ride, the angles over 90° are predicted.…”
Section: Discussionmentioning
confidence: 99%
“…According to the above described use of vibrations Yu et al (2015) state that an angle of 90° provides better flexibility of the knee, and the r.m.s. results show the value of 0.904 ± 0.454 m.s -2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that the low ISO‐weighted average frequency of horseback WBV (range 2.5–3.6 Hz) may impose discomfort and may relate to deleterious health effects on the lumbar spine, which has a natural resonant frequency of 4–12 Hz [Pope and Novotny, ; Chaffin et al, ]. However, in a highly controlled context, low‐magnitude but high‐frequency vibration from horseback riding may also provide some therapeutic benefit, particularly when considering the recreational effect and its anabolic effects on the bone and muscle strength as well as balance [Whalen and Case‐Smith, ; Wehrle et al, ; Yu et al, ].…”
Section: Discussionmentioning
confidence: 99%